Antena de microfita com sobrecamada de cera de carnaúba - Queiroz, Stefany Kariny dos Santos de Souza (Universidade Federal Rural do Semi-Árido, 2019)
The growing development of telecommunications, particularly mobile devices, has stimulated research related to microfite antennas in recent years, since they are the key elements in the signal transmission and reception chain. These antennas are advantageous because they are discrete, mountable to a variety of surfaces, simple to construct, inexpensive, mechanically compatible with monolithic microwave integrated circuit (MMIC) designs, and design versatility. The study of new materials such as ferrite, thin films, metamaterials, among others, for various applications, whether through doping, composite blends or the use of multilayers in antennas, is a growing aspect. Considering the abundance of carnauba wax, which comes from a palmaceous species, and because it has social, economic and cultural relevance in the northeastern semiarid scenario, this work deals with the application of carnauba wax as an overlay (or super layer) for rectangular antennas of microfita. The interest of the work is to understand the electromagnetic behavior of the multilayer in microfite antennas. The carnauba wax used in the project had previously been characterized in another work. Its use in deposition on the antenna requires a technique of melting and slow cooling, this being a ready critic. In this work, a standard rectangular microfita antenna was initially designed by the transmission line method, after which the antenna was simulated in Ansoft HFSS (High FrequencyStructural Simulator): the standard antenna and the projected antenna with carnauba wax overlay, for the study of interest. With the simulation, it was possible to obtain the radiation diagrams (2D and 3D), loss of return, Smith chart and gain for both antennas, so that it was possible to compare them, and finally they were made so that it could be tested, and validate the design and simulation data. The simulated results of the antennas were performed to resonate at the 2.45 GHz frequency. Subsequently the simulation and antenna tests showed a good agreement of the simulated and measured results, observed through the return loss diagram and the Smith. Another important point that was observed was a significant increase in the return loss of the antenna with the wax overlay when compared to the standard antenna.
Monografia
Keywords: Antena de Microfita; Cera de carnaúba; Material orgânico; ENGENHARIAS::ENGENHARIA ELETRICA